Structural peculiarity of Antarctic fish hemoglobins - MAZZARELLA, LELIO; VERGARA, ALESSANDRO; MERLINO, ANTONELLO; M. FRANZESE; L. VITAGLIANO; C. VERDE; G. DI PRISCO (2005)
Over the last two decades several crystal structures of Antarctic fish hemoglobins (AFH) have been determined. Here we review the most relevant results. The hemichrome formation has been proved as a property common to every AFH, and the current results are here presented in contrast to the mammalian hemoglobins (Hbs). Furthermore, many AFH exhibit the Root effect, a drastic reduction in oxygen-carrying capacity and cooperativity occurring at acidic pH, a property common to many fish Hbs. Despite the longstanding problem, a general structural explanation of the Root effect is still pending. Recent advances have re-opened the question and new perspectives leading us toward a solution are presented.